Small arms and light weapons: the disjunction problem. Issue 2 (4th March 2019) - Alley, Roderic
ABSTRACT: Growing in range and urgency, humanitarian needs now pose increasingly acute questions for national security policy formulation. Whether over forced migration, food scarcity or nefarious electronic penetration, state security preferences face uneasy accommodations with individual needs be it for child survival, basic sustenance or rights to privacy. This paper deliberates a further field of increasingly apparent value contest: that involving the transfer, diversion and lethal use of small arms and light weapons (SALW). After outlining the scale of this phenomenon, existing regulatory mechanisms over SALW transfers are assessed. It is argued that these controls are inadequate, a deficiency that is embedded within a range of inter-linked disjunctions. They are outlined in a model that is evaluated against empirical findings. Where SALW control inadequacy is causally connected to the disjunctive model, it is argued, current levels of SALW-induced casualties are unlikely to abate. The paper concludes by considering feasible options for enhanced management of global SALW proliferation.